The Sn-3.5Ag-1.0Cu-0.1Zn/Cu intermetallic interface under thermal aging / Iziana Yahya, Hamidi Abd Hamid and Ramani Mayappan - Yahya, Iziana; Abd Hamid, Hamidi; Mayappan, Ramani (Universiti Teknologi MARA, Perlis, 2012)
Due to environmental concerns, lead-free solders were introduced to replace the lead-based solders in microelectronics devices technology. Although there were many lead-free solder available, the Sn-Ag-Cu was considered as the best choice. But the solder has its draw backs in terms of melting temperature and intermetallic formations. To improve the solder, a fourth element Zn was added into the solder and was synthesized via powder metallurgy route. This research studies the effect of 0.1wt% Zn addition on the mechanical properties and intermetallic formation on Cu substrate. For the mechanical test, the Vickers hardness (Hν), yield strength (σy) and ultimate tensile strength (σUTS) were reported. The mechanical test for Zn based composites solder shows better properties compared to un-doped counterparts. For intermetallic, the solders were melted at 250oC and aged at 150oC until 400 hours. The phases formed and its growth was studied under SEM and by energy dispersive x-ray (EDX). The addition of Zinc has improved the mechanical properties of Sn-Ag-Cu solder, while the SEM results show the presence of Cu6Sn5 and Cu3Sn intermetallics. The addition of 0.1wt% Zn has retarded the growth of the Cu3Sn intermetallic but not the total intermetallic thickness.